Logistic regression analysis of risk factors for pediatric burns: a case–control study in underdeveloped minority areas in China - Lin, Ziren; Iyappan, Petchi; Huang, Zhiqun; Sooranna, Suren Rao; Wu, Yongfang; Lan, Liuting; Huang, Cheng; Liang, Feiteng; Zhao, Daji; Huang, Dingjin (Frontiers in Pediatrics, 2024)
Background: Pediatric burns are common, especially in underdeveloped countries and these can physically affect the children involved and have an impact on their mental health. This study aimed to assess the effect of pediatric burns in underdeveloped minority areas of China.Methods: Case information from 192 children was collected for outpatient and inpatient clinics by using a survey questionnaire. These included 90 pediatric burn cases and 102 controls who were children without burns. Stepwise logistic regression analysis was used to determine the risk factors for pediatric burns in order to establish a model. The goodness-of-fit for the model was assessed by using the Hosmer and Lemeshow test as well as ROC and internal calibration curves. A nomogram was then used to analyze the contribution of each influencing factor to the pediatric burns model.Results: 7 variables including gender, age, ethnic minority and the household register, mother working status, mother education and number of children were analyzed for both groups of children. Of these age, minority, mother's working status and number of children in a household were found to be related to the occurrence of pediatric burns by univariate logistic regression analysis (P <0.05). After collinearity diagnosis, multivariate logistic regression analysis of variables with tolerances of > 0.2 and VIF <5 showed that age was a protective factor for pediatric burns (OR=0.725; 95% CI: 0.665-0.801). Compared with single-child parents, those with 2 children were at greater risk of pediatric burns (OR=0.389; 95% CI: 0.158-0.959). The ethnic minority of the child and the employment status of the mother were also risk factors (OR=6.793; 95%CI: 2.203-20.946 and OR= 2.266; 95% CI: 1.025-5.012, respectively). Evaluation of the model used was found to be stable. A nomogram showed that the contribution in the children burns model was age＞mother working status＞number of children＞minority.Conclusions: This study showed that there are several risk factors strongly correlated to pediatric burns including age, ethnic minority, the number of children in a household and the mother's working status. Government officials should direct their preventative approach to tackling the problem of pediatric burns by promoting awareness of these findings.